2014
DOI: 10.1002/chem.201304165
|View full text |Cite
|
Sign up to set email alerts
|

Two Series of Sandwich Frameworks Based on Two Different Kinds of Nanosized Lanthanide(III) and Copper(I) Wheel Cluster Units

Abstract: Two series of sandwich frameworks, [La6(μ3-OH)2(ox)3L12Cu11(μ3-X)6(μ2-X)3]·8H2O (X=Br/Cl, FJ-21 a/b; L=4-pyridin-4-yl-benzonate; ox=oxalate) and [Ln4(OAc)3-(H2O)4L9][Cu(μ3-I)]@[Cu10(μ3-I)(μ4-I)6(μ5-I)3]·7H2O (Ln=Pr/Nd/Sm/Eu, FJ-22 a/b/c/d; OAc=acetate) have been hydrothermally prepared. These sandwich frameworks are assembled by two different kinds of nanosized lanthanide-(III) and copper(I) wheel cluster units, La18 and 3Cu@Cu24 in FJ-21, Ln24 and Cu2@Cu24 in FJ-22. The synergistic coordination between organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 68 publications
1
26
0
1
Order By: Relevance
“…The skeleton of Eu 3 SBUs are retained when Ln oxide and oxalate was replaced by lanthanum oxalate. [11] Thet ripodal Eu 3 nodes are extended by m 4 -ox ligandst of orm aE u 18 FJ-23 wheel layer (Figure 1a), which is comparablet ot he famous6 3 graphene-like layers. Despite similar Ln SBUs is found in the formerly reported FJ-21,t here are still some differences between the two Ln wheelso wing to lanthanide contraction ( Figure S3, SupportingI nformation).…”
Section: Fj-24mentioning
confidence: 75%
See 3 more Smart Citations
“…The skeleton of Eu 3 SBUs are retained when Ln oxide and oxalate was replaced by lanthanum oxalate. [11] Thet ripodal Eu 3 nodes are extended by m 4 -ox ligandst of orm aE u 18 FJ-23 wheel layer (Figure 1a), which is comparablet ot he famous6 3 graphene-like layers. Despite similar Ln SBUs is found in the formerly reported FJ-21,t here are still some differences between the two Ln wheelso wing to lanthanide contraction ( Figure S3, SupportingI nformation).…”
Section: Fj-24mentioning
confidence: 75%
“…FJ-23 and FJ-24 are closely related to the previouss andwiched cluster organic frameworks built by Ln wheelc lusters, such as FJ-2, [9] FJ-4, [10] FJ-21, [11] and FJ-22. [11] First of all, they all crystallize in the trigonal/hexagonal crystal system and possess al arge unit cell (Table 1). Then, graphene-like Ln wheelsa re all included:E r 36 in FJ-2,L n 18 in FJ-4,L a 18 in FJ-21,L n 24 in FJ-22, Eu 18…”
Section: Fj-24mentioning
confidence: 93%
See 2 more Smart Citations
“…Because of the simultaneous existence of the hard-base carboxylate group and the soft-base N-atom donor of the pyridyl ring, many pba-based MOFs with different topologies, like dia (Mehlana et al, 2012;Zhou et al, 2012;Elsaidi et al, 2014;Zeng et al, 2013;Zhang et al, 2017;Wang et al, 2017), pcu (Das et al, 2011;Zhang et al, 2011;, rtl (Zhou et al, 2014), tsi (Chen et al, 2016), hxl (Fang et al, 2013), bcu (Zeng, Zhou et al, 2010;Zhou et al, 2015), fsc (Elsaidi et al, 2016), ncb (Zhang et al, 2009(Zhang et al, , 2012Zhao, Mao et al, 2016), bnn (Fang, Zhang et al, 2015), tfz-d (Liu, Luo et al, 2014), mdf (Wang, Fang et al, 2010), sql , pts and qtz (Mehlana et al, 2013), have been reported. Moreover, a few novel topological pba-based MOFs with the Schlä fli symbols (3 6 Á4 18 Á5 3 Á6) (Ding et al, 2017), (8 4 Á12 2 )(8) 2 (Wang et al, 2018), and (3 3 Á4 12 Á5 3 Á6 3 )(3 6 Á4 12 Á5 9 Á6) (Fang, Cheng et al, 2014) have been known. However, substituted pba ligands remain less developed with respect to the construction of MOFs.…”
Section: Introductionmentioning
confidence: 99%